2009
DOI: 10.1097/bsd.0b013e318192d8ad
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Changes After Various Anterior Approaches in the Treatment of Adolescent Idiopathic Scoliosis

Abstract: Slight declines in pulmonary function at 2-year follow-up were noted in both the thoracotomy and thoracoscopic groups, but to a significantly greater extent in those with an open thoracotomy. Significantly greater impairment in pulmonary function was seen in thoracoscopic patients who underwent thoracoplasty, whereas those without thoracoplasty either had no significant declines at 2 years or experienced slight but significant improvement. No significant diminishment was noted for the thoracoabdominal approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Serial measures of lung function in older children with scoliosis treated with transthoracic spine surgery have shown greater loss of function postoperatively when the thorax is opened. 54 …”
Section: Compression-based Implantsmentioning
confidence: 99%
“…Serial measures of lung function in older children with scoliosis treated with transthoracic spine surgery have shown greater loss of function postoperatively when the thorax is opened. 54 …”
Section: Compression-based Implantsmentioning
confidence: 99%
“…Lonner et al [8] reported in a multicenter study comparing various methods of anterior approach in correction of idiopathic scoliosis. Their result showed a slight reduction in pulmonary function in open thoracotomy group.…”
Section: Discussionmentioning
confidence: 99%
“…Results of both have been reported in the literature [3][4][5][6]. One of the main concerns of the anterior instrumentation of thoracic spine is the possible compromise of pulmonary function [3,[7][8][9][10]. In the thoracoscopic method a complete disc removal, involving the complete removal of the posterior annulus, is technically impossible.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that more than 50 % of patients undergoing the open thoracotomy approach will demonstrate at least a 15 % decrease in pulmonary function tests at the 2-year follow-up [26]. The thoracoabdominal approach does not produce significant lung volume changes [27,28]. The pulmonary function effects of thoracoscopic instrumentation without thoracoplasty are somewhat contradictory with one study reporting no effects [27] and others reporting detrimental effects ([15 % decline in pulmonary function tests) in about 15 % of patients [26,29].…”
Section: Anterior Thoracoscopic Proceduresmentioning
confidence: 99%